1980
DOI: 10.1038/287198a0
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of an avian sarcoma virus oncogene (src) and proposed amino acid sequence for gene product

Abstract: The transforming gene (src) of avian sarcoma virus (ASV) and adjacent regions of the viral genome have been isolated by molelcular cloning of viral DNA. Their nucleotide sequence encompasses the whole of src and the portion of the gene env that encodes gp 37, one of two glycoproteins found in the viral envelope. Src encodes a single, hydrophobic protein with structural features that conform to previous descriptions descriptions of the gene product (pp60src). It appears that a single viral protein is responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
136
0
1

Year Published

1984
1984
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(141 citation statements)
references
References 40 publications
4
136
0
1
Order By: Relevance
“…The DNAs encoding v-Src (coding region from pGDvSrc Schmitt-Ruppin A Rous sarcoma virus oncogene 36,37 ), human C-terminal Src kinase (Csk) 38 (2.4 kb Sma I fragment, provided by Dr. D.O. Morgan, University of California, San Francisco, CA), rat STAT1␣, STAT3, STAT5, 39 STAT3 ⌬ 55C, 40 mouse STAT4, 41 and human STAT6 42 were subcloned as Not I fragments into pDC vector.…”
Section: Methodsmentioning
confidence: 99%
“…The DNAs encoding v-Src (coding region from pGDvSrc Schmitt-Ruppin A Rous sarcoma virus oncogene 36,37 ), human C-terminal Src kinase (Csk) 38 (2.4 kb Sma I fragment, provided by Dr. D.O. Morgan, University of California, San Francisco, CA), rat STAT1␣, STAT3, STAT5, 39 STAT3 ⌬ 55C, 40 mouse STAT4, 41 and human STAT6 42 were subcloned as Not I fragments into pDC vector.…”
Section: Methodsmentioning
confidence: 99%
“…For some time, there was a controversy as to whether this activity was intrinsic to Src or merely associated with it. This controversy was finally laid to rest when both v-Src and the catalytic chain of the cyclic AMPdependent protein kinase had been cloned and sequenced (Czernilofsky et al, 1980(Czernilofsky et al, , 1983Shoji et al, 1981;Takeya and Hanafusa, 1982;Schwartz et al, 1983) and were found to be to be homologous (Barker and Dayhoff, 1982).…”
Section: The V-src Proteinmentioning
confidence: 99%
“…The discovery of the cellular form of Src kinase, pp60 c-src , or c-Src, in uninfected cells (Collett et al, 1979;Oppermann et al, 1979), followed by molecular cloning and sequencing of the chicken c-src gene (Parker et al, 1981;Shalloway et al, 1981;Takeya et al, 1982) and the RSV v-src gene (Czernilofsky et al, 1980(Czernilofsky et al, , 1983 led to the ®nding that the cellular c-Src and RSV v-Src proteins were closely related but that they di ered substantially at their carboxy-termini (Takeya and Hanafusa, 1983). In particular, although c-Src and v-Src exhibited several single amino acid di erences, the most striking di erence was the replacement of the carboxy-terminal 19 amino acids of chicken c-Src by 12 completely di erent amino acids in RSV v-Src.…”
Section: Introductionmentioning
confidence: 99%